EFFECTIVENESS OF SUPERVISION TO IMPROVE TEACHER DISCIPLINE IN THE PAI LEARNING PROCESS AT SMKN 4 TEBING TINGGI - Khairun Nikmah; Amini, Amini; Nurzannah, Nurzannah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
The purpose of this study is to evaluate how well supervision works at SMKN 4 Tebing Tinggi to improve teacher discipline during the PAI learning process. At SMKN 4 Tebing Tinggi, this kind of research employs a case study methodology along with a qualitative approach. The period of this investigation was December 2023–March 2024. instructors that teach PAI, guidance and counseling instructors, homeroom teachers, deputy principals for student affairs, members of the local community, and school principals served as research informants. Methods such as observation, interviews, and documentation studies were used to gather data. The study's findings indicate that, in order for teachers to assess their own work discipline, there is a clear impact of the interpreter modis program (teacher journals for monitoring and discipline). First, teachers' discipline is well-organized. Second, the instructor sets a clear example (exemplary) of discipline, such as being punctual and dressing nicely, so that pupils can successfully emulate it. Because teachers serve as role models for kids in the classroom, the